Analysis of 18th- and 19th-Century Musical Works in the Classical Tradition. - Beach, David (Taylor & Francis, 2012)
Analysis of 18th- and 19th-Century Musical Works in the Classical Tradition is a textbook for upper-level undergraduate and graduate courses in music analysis. It outlines a process of analyzing works in the Classical tradition by uncovering the construction of a piece of music-the formal, harmonic, rhythmic, and voice-leading organizations-as well as its unique features. It develops an in-depth approach that is applied to works by composers including Haydn, Mozart, Beethoven, Schubert, Schumann, and Brahms. The book begins with foundational chapters in music theory, s.